2016
DOI: 10.13005/ojc/320644
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties and Chemical Composition of the Rice Husk and Dust

Abstract: The paper deals with the physical properties and chemical composition of rice husk and dust, which are the waste of the Regulus raw rice growing in the Krasnodar Region of the Russian Federation. Rice dust is formed as a result of the discharge upon the receipt of raw rice from vehicles, removal of impurities, sorting by size, during separation of membranes, crushing, grinding, polishing, moving grain along the elevators and conveyors, i.e. during all technological operations production of rice groats. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…Changes in the respective weight of the active mixed metal oxides after adsorption revealed their positive influence on the BGD adsorption on the active sites of calcined SS-RH particles. A study also revealed silicon and calcium composition to be 32.2 and 10.21 wt% whose sources were from rice husk and snail shell respectively (Korotkova et al., 2016). Reduction in wt% of active oxides of Si, Al and S in the calcined SS-RH particles suggested their strong affinity to adsorb BGD from aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in the respective weight of the active mixed metal oxides after adsorption revealed their positive influence on the BGD adsorption on the active sites of calcined SS-RH particles. A study also revealed silicon and calcium composition to be 32.2 and 10.21 wt% whose sources were from rice husk and snail shell respectively (Korotkova et al., 2016). Reduction in wt% of active oxides of Si, Al and S in the calcined SS-RH particles suggested their strong affinity to adsorb BGD from aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Exhibit b revealed the positive influence of the active mixed metal oxides on the BGD adsorption as a result of changes in their respective weight percents after adsorption. Similar studies have also revealed larger compositions of 32.2 and 10.21 weight percent for silicon and calcium to be originated from the rice husk and snail shell, respectively (Korotkova, Ksandopulo, Donenko, Bushumov, & Danilchenko, ). Reduction in weight percent of the active oxides of Si, Al, and S in the SS‐RH composite adsorbent revealed their strong affinity to adsorb BGD from an aqueous solution.…”
Section: Resultsmentioning
confidence: 71%
“…The result of energy dispersive spectroscopy analysis showing elemental weight percent of adsorbent before and after Cd(II) adsorption from aqueous is presented in Table 7. The larger weight percent of calcium (13.21%) and silicon (21.20%) could be traced to walnut shell and rice husk respectively (Korotkova et al., 2016) while presence of iron (38.85%) is a strong evidence of their magnetization before Cd(II) adsorption. The following observations are strong evidence of Cd(II) sorption onto NM-WS-RH-AC (1) changes in the weight percent of adsorbent elemental composition (Popoola, 2019) (2) reduction in oxygen and hydrogen content implies H + and OH − reaction has occurred on adsorbent surface and (3) presence of cadmium in the adsorbent (found missing before adsorption) after adsorption.…”
Section: Resultsmentioning
confidence: 99%